The Catalytic Degradation Performance of α-FeOOH Doped with Silicon on Methyl Orange - Yonghua Lu; Weiwei Gao; Fang Xu; Guangxian Zhang; Fengxiu Zhang (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2016)
In order to improve the catalytic degradation property of α-FeOOH, α-FeOOH was doped with sodium silicate. The α-FeOOH doped with silicon was used as catalyst to catalyze the degradation of methyl orange. The XRD spectra showed that the crystalline phase of α-FeOOH doped with silicon was same as that of α-FeOOH; The catalytic degradation property of α-FeOOH doped with silicon was 21.7% higher than that of α-FeOOH; The results showed that catalytic degradation of methyl orange was almost degraded thoroughly at the conditions that the concentration of α-FeOOH doped with silicon in the solution was 0.73 g/L, the concentration of H2O2 was 0.231 mmol/L. The pH value was between 2 and 3, and the degradation reaction was carried out at 60 oC for at least 20 min.